Profile of 3 years and 4 years vocational school Relationship with the preparation of graduates Building engineering expertise program - Pratama, Sheila Ayu; Winanti, Elizabeth Titiek; Wardhono, Arie (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine differences (1) curriculum structure; (2) industrial work practices; (3) graduate work readiness; and (4) the absorption of graduates between 3-year Vocational Schools and 4-year Vocational School building engineering expertise programs. The research method used was descriptive research with ex post facto approach and survey. Data collection techniques in this study used documentation, interviews and online questionnaires.  The results of this study are as follows: (1) the learning burden on 3-year Vocational High Schools is 5016 JP and 413 KD while the 4-year Vocational School is 6648 JP and 443 KD; (2) apprenticeship implemented at 3 Years Vocational School for 3 months and 4 Year Vocational School for 6-8 months; (3) 3-year SMK graduates 60% of whom are declared ready for work, while 4-year SMK graduates 71.80% of whom are declared more ready to work; and (4) 70% of 3-year vocational school graduates work in a field, while 92% of 4-year SMK graduates work in a field. This can explain that it will be more effective if the Vocational School is held with a 4-year SMK pattern.